Expression of specific ionotropic glutamate and GABA-A receptor subunits is decreased in central amygdala of alcoholics - Jin, Zhe; Bhandage, Amol K.; Bazov, Igor; Kononenko, Olga; Bakalkin, Georgy; Korpi, Esa R.; Birnir, Bryndis (Frontiers in Cellular Neuroscience, 2014)
The central nucleus of amygdala (CeA) has a role for mediating fear and anxiety responses. It is also involved in emotional imbalance caused by alcohol abuse and dependence and in regulating relapse to alcohol abuse. Growing evidences suggest that excitatory glutamatergic and inhibitory γ-aminobutyric acid-ergic (GABAergic) transmissions in the CeA are affected by chronic alcohol exposure. Human post-mortem CeA samples from male alcoholics (n=9) and matched controls (n=9) were assayed for the expression level of ionotropic glutamate and GABA-A receptors subunit mRNAs using quantitative real-time reverse transcription-PCR (RT-qPCR). Our data revealed that out of the 16 ionotropic glutamate receptor subunits, mRNAs encoding two AMPA [2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propanoic acid] receptor subunits GluA1 and GluA4; one kainate receptor subunit GluK2; one NMDA (N-methyl-D-aspartate) receptor subunit GluN2D and one delta receptor subunit GluD2 were significantly decreased in the CeA of alcoholics. In contrast, of the 19 GABA-A receptor subunits, only the mRNA encoding the α2 subunit was significantly down-regulated in the CeA of the alcoholics as compared with control subjects. Our findings imply that the down-regulation of specific ionotropic glutamate and GABA-A receptor subunits in the CeA of alcoholics may represent one of the molecular substrates underlying the new balance between excitatory and inhibitory neurotransmission in alcohol dependence.